2016
DOI: 10.1111/ajco.12464
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health‐related quality of life between European and Asian patients with hepatocellular carcinoma

Abstract: Both clinical characteristics and geographic areas affected the HRQoL in with hepatocellular carcinoma. Cultural differences and clinical differences in the pattern of disease due to active surveillance of Asian countries may explain the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Also, significant changes in QoL have been observed across different cultures. 129 Defining and evaluating reliable QoL assessment tools has been established as one of the unmet needs in HCC research by international guidelines. 4 In summary, health-related QoL measures are not ready to support, as single tools, regulatory approval for drugs in HCC.…”
Section: Key Pointmentioning
confidence: 99%
“…Also, significant changes in QoL have been observed across different cultures. 129 Defining and evaluating reliable QoL assessment tools has been established as one of the unmet needs in HCC research by international guidelines. 4 In summary, health-related QoL measures are not ready to support, as single tools, regulatory approval for drugs in HCC.…”
Section: Key Pointmentioning
confidence: 99%
“…Many studies showed a marked discrepancy between reported HRQoL data in the results section and the frequency of HRQoL data assessment specified in the methods section. Eight studies reported only baseline HRQoL data although these trials specified in their methods section to have assessed HRQoL also during follow-up [ 38 , 41 , 42 , 58 , 80 , 94 , 98 , 139 ]. The other 18 studies lacked reporting of HRQoL data altogether in their results section, although assessment had been announced in the methods section (supplement 3) [ 25 , 28 , 31 , 44 , 50 , 53 , 56 , 66 , 71 , 74 , 75 , 80 , 95 , 97 , 112 , 134 , 136 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, nine publications combined patient groups undergoing different treatment options (surgery/medical therapy/interventional treatment) for the reporting of HRQoL outcomes. In these cases, assignment of HRQoL outcomes to a specific treatment (surgery vs. medical therapy vs interventional treatment) was impossible [ 28 , 42 , 56 , 58 , 87 , 88 , 120 , 127 , 132 ]. In summary, only three studies remained for quantitative analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis was driven by findings reported by previous studies that demonstrate geographic areas effect HRQoL in HCC. Specifically, Asian patients with HCC report significantly better scores in HCC18 scales (sexual interest, fatigue) than European patients [ 31 ]. It has been posited that these differences in scores stem from variability in management practices between Europe and Asia (i.e., active surveillance programs implemented in Asia) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%